Development of the 3-point field goal in basketball: A descriptive statistical analysis of participating national teams of European championships from 1985 to 2007 - Papadopoulos, P.; Lindner, M.; Friedel, B.; Goebel, L.; Stafilidis, S.; Schmidt, G. J.; Baum, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The international governing body of basketball (FIBA) introduced the three-point line in 1984. The purpose of this study was to investigate the development of the 3-point field goal (3FG) at the European Championships (EC) from 1985 to 2007. Methods: The shooting performance of 166 teams (530 games) which participated in the EC from 1985 to 2007 was evaluated to discover the development of the 3FG. The statistics were taken from official resources (FIBA Europe). The detailed 3-point shooting quotas of all teams were compared to the total shooting performances of all teams for each investigated tournament. Descriptive statistics were used for data analyses. Results: The lowest number of attempted (3PA) and made 3-point shoots (3PM) was found in 1985 (10.8 ± 5.2; 4.2 ± 2.4). 2007 almost two times more 3PA (21.8 ± 4.7) were found than 1985. Great increases of 3PA and 3PM were detected in 1987 (4.3; 1.6) and 2001 (4.8 and 1.1). From 1985 to 1993 the 3-point shoot percentage (3P%) was on a high level (38.0%-43.0%), with the maximum of 43% in 1991. From 1993 to 1997 a decrease to 33.8% was shown. Since then the 3P% was on a lower level (32.7%-37.3%). The least percentage of points from 3PM/total points (3PP/TP) was observed in 1985 (13.7%) and the highest value in 2007 (30.3%). Great rises of 3PP/TP were recognized in 1987 (5.6%) and 1999 (4.9%). Discussion: The low number of 3PA and 3PM at the EC 1985 may be a consequence of the 3-point rule introduction in 1984. At this point players and teams weren`t well enough trained technically and tactically. The high increases of 3PA and 3PM in 1987 was a precondition for the rise of 3PP/TP at the same time and could be considered as a result of the training progress. The rise of these values from 1985 to 1987 can be interpreted as a fast integration of the 3FG in the offensive tactics. The fact that the 3P% raised until 1991 emphasised this assumption. Different strategic directions on defence and offence should be considered as a reason for the decrease of the 3P% from 1993 to 1997. They could also be responsible for the increased 3PP/TP in 1999 and the fact that in 1999 25% of the total points and in 2005 28% of the total points were made by 3FG. The rise of 3PA and 3PM in 2001 can be explained by the increased number of total field goal attempts and number of total 3PA in consequence of the reduced possession time in offence to 24 sec. Further studies should be conducted examining the effects of the